De eerste-steen legging. V.l.n.r. achter tafel: Roemers, ? de Vrankrijker, ?, ?. Voor de tafel: van Arkel
De eerste-steen legging. V.l.n.r. achter tafel: Roemers, ? de Vrankrijker, ?, ?. Voor de tafel: van Arkel.